Evaluating the Antibiotic Susceptibility of Chlamydia – New Approaches for in Vitro Assays - Marti, Hanna; Borel, Nicole; Dean, Deborah; Leonard, Cory A. (Frontiers in Microbiology, 2018)
Pigs are the natural hosts of Chlamydia suis, the only Chlamydia species known to spontaneously acquire homotypic resistance conferred by a class C tetracycline resistance gene. Various susceptibility assays have existed for several years, but there is no widely accepted, standardized assay to determine chlamydial antibiotic susceptibility. In this study, we developed new approaches to determine the in vitro susceptibility of Chlamydia to different antibiotics in view of existing protocols. Specifically, the minimal inhibitory concentration (MIC) is based on a consensus of both inclusion number reduction and alteration of inclusion size and morphology upon antibiotic exposure. In addition to these, we employed a recovery assay, allowing observation of the chlamydial response to drug removal and subsequent recovery, as compared to both continued exposure and to the unexposed control. We propose a simple and fast screening method to detect tetracycline resistant C. suis strains within 2 to 3 days with minimal use of consumables. For proof of principle, we evaluated the susceptibility of three C. suis field strains and the reference strain S45/6 to tetracycline, sulfamethoxazole, and penicillin, antibiotics commonly used to prevent respiratory and gastrointestinal diseases on fattening pig farms. We found that tetracycline sensitive strains can easily be distinguished from resistant strains using the evaluation parameters proposed in this study. Moreover, we report that S45/6 is sensitive to sulfamethoxazole while all evaluated C. suis field strains showed some degree of sulfamethoxazole resistance. Finally, we confirm that Penicillin G induces the chlamydial stress response in all evaluated C. suis strains.